Interdependency of plants and animals in controlling the sodium balance of ecosystems and the impacts of global defaunation. Issue 2 (15th October 2015) - Doughty, Christopher E.; Wolf, Adam; Baraloto, Christopher; Malhi, Yadvinder
Abstract : Sodium, an element which is needed by animals but often toxic in high concentrations to plants, may be deficient and limit animal abundance in inland continental regions, but may be overabundant and limit plant productivity in coastal regions. Here we present data from 50 independent plots (including leaf data from more than 2480 individual trees) showing that leaves in the Amazon basin uptake high amounts of sodium (Na) in a manner more similar to the essential cation potassium (K) than to the toxic cation aluminium (Al). Leaf Na increases linearly with soil Na concentrations, and there is no apparent mechanism for selective exclusion of Na in comparison to K, a key attribute of halophytes. This indicates that the Amazon basin is broadly non‐halophytic and increased sodium concentrations in non‐halophyte plants often decrease plant productivity. Total Na concentrations are ∼ 10 times higher in coastal regions than inland regions. Such concentration gradients in nutrients may have been reduced in the past because large animals that were abundant in the Pleistocene have been hypothesized to play a large role in reducing nutrient concentration gradients at continental scales. We use a diffusion model and a Na loss rate based on empirical data to estimate that large animals may have moved significant quantities of Na inland away from coastal regions in the Amazon Basin. Therefore, our simple model suggests that large animals may play an important, yet diminishing, role in maintaining the sodium balance of the planet.